Understanding Factors that Shape Gender Attitudes in Early Adolescence Globally: A Mixed-Methods Systematic Review. - Anna Kågesten; Anna Kågesten; Susannah Gibbs; Robert Wm Blum; Caroline Moreau; Venkatraman Chandra-Mouli; Ann Herbert; Avni Amin (PLoS ONE, 2016)
Background Early adolescence (ages 10-14) is a period of increased expectations for boys and girls to adhere to socially constructed and often stereotypical norms that perpetuate gender inequalities. The endorsement of such gender norms is closely linked to poor adolescent sexual and reproductive and other health-related outcomes yet little is known about the factors that influence young adolescents' personal gender attitudes. Objectives To explore factors that shape gender attitudes in early adolescence across different cultural settings globally. Methods A mixed-methods systematic review was conducted of the peer-reviewed literature in 12 databases from 1984-2014. Four reviewers screened the titles and abstracts of articles and reviewed full text articles in duplicate. Data extraction and quality assessments were conducted using standardized templates by study design. Thematic analysis was used to synthesize quantitative and qualitative data organized by the social-ecological framework (individual, interpersonal and community/societal-level factors influencing gender attitudes). Results Eighty-two studies (46 quantitative, 31 qualitative, 5 mixed-methods) spanning 29 countries were included. Ninety percent of studies were from North America or Western Europe. The review findings indicate that young adolescents, across cultural settings, commonly express stereotypical or inequitable gender attitudes, and such attitudes appear to vary by individual sociodemographic characteristics (sex, race/ethnicity and immigration, social class, and age). Findings highlight that interpersonal influences (family and peers) are central influences on young adolescents' construction of gender attitudes, and these gender socialization processes differ for boys and girls. The role of community factors (e.g. media) is less clear though there is some evidence that schools may reinforce stereotypical gender attitudes among young adolescents. Conclusions The findings from this review suggest that young adolescents in different cultural settings commonly endorse norms that perpetuate gender inequalities, and that parents and peers are especially central in shaping such attitudes. Programs to promote equitable gender attitudes thus need to move beyond a focus on individuals to target their interpersonal relationships and wider social environments. Such programs need to start early and be tailored to the unique needs of sub-populations of boys and girls. Longitudinal studies, particularly from low-and middle-income countries, are needed to better understand how gender attitudes unfold in adolescence and to identify the key points for intervention.